FAKTOR YANG MEMPENGARUHI MINAT DAN DAMPAKNYA TERHADAP KEPUTUSAN PESERTA BPJS KETENAGAKERJAAN DALAM MENGGUNAKAN ELECTRONIC WALLET (E-WALLET) - Intansari, Hasvina; Zulfadil, Zulfadil; Ganasih, Raden Lestari (Komunitas Manajemen Kompetitif, 2024)
The purpose of the study was to analyze the effect of perceived risk, perceived usefulness, perceived ease of use on intention to use e-wallet for pay a bill of BPJS Ketenagakerjaan. To analyze intention to use on usage decision as intervening variable. And to analyze the influence of perceived risk, perceived usefulness, perceived ease of use on participants' decisions through participant interest. In this study, the population in this study is the participation of BPJS Ketenagakerjaan Cabang Pekanbaru Kota, namely 5,657 business entities represented by PIC / Business Entity Officers registered in BPJS Ketenagakerjaan. The sample in this study requires around 366 respondents. The data used in this study were primary data and secondary data, while the data collection technique used questionnaires. The data analysis technique used in this study is Data analysis used in this study is SEM. The results showed that risk perception, benefit perception and ease of use perception of e-wallet applications have a significant influence and impact on intention used of e-wallets. Intention of used has a significant influence on the decision to use e-wallet applications. Risk perception, benefit perception and e-wallet application usage perception have a significant influence on e-wallet application usage decisions through e-wallet intention to used. Keywords: Perceived Risk, Perceived Usefulness, Perceived Ease Of Use, Intention of used And Decision of Used, BPJS Ketenagakerjaan.